'Wadi et al. adsorption data set - Effect of combined primary and secondary amine loadings on the adsorption mechanism of CO2 and CH4 in biogas' - Wadi, Basil; Nabavi, Seyed Ali; Golmakani, Ayub; Manovic, Vasilije (Cranfield University, 2021)
Data set for amine functinalised SBA-15 with primary, diamine and triamine reagents. The attached data includes volumetric gas adsorption and TGA adsorption results for CO2 and CH4, and associated with the publication listed above.
Keywords: 'carbon capture'; 'amine functionalised'; 'sba-15'; 'biogas'; 'amines'; 'ch4'; 'co2'; 'separation'; 'selectivity'; 'Carbon Capture Engineering (excl. Sequestration)'